The Effect of Wages on Employee Satisfacation of Juan Racing Gear in Garut District - Siahaan, Nadia Oktavian; Budiman, Arief; Rachmani, Nizza Nadya (A Social Science and Entrepreneurship Journal, 2022)
This study aims to determine that there is an effect of wages on employee job satisfaction. the purpose of this study is to determine the effect of wages on employees Juan Racing Gear Satisfaction in Garut Regency The object of this research is Juan Racing Gear in Garut Regency. Juan Racing is a Micro, Small and Medium Enterprise (MSME) which was founded in 2013, and is engaged in fashion. This study uses two variables, namely wages as the X variable or the independent variable and job satisfaction as the Y variable or the dependent variable. This research was conducted with quantitative methods. The result of this study is that wages have a positive effect on employee job satisfaction at Juan Racing Gear SMEs.